Production Optimization Through the Material Requirement Planning (MRP) Method in The Nias Tofu Product Business in Onomamolo Village I Lot - Solfin Desmeni Mendrofa; Serniati Zebua; Martha Surya Dinata Mendrofa; Jeliswan Berkat Iman Jaya Gea (Economics and Business Journal (ECBIS), 2025)
The main objective of this study is to compare and analyze the effectiveness of the MRP (Material Requirement Planning) method in optimizing raw material inventory management in the Nias Tofu business. This study uses a mixed method. Primary data in this study were obtained directly from the Nias Tofu business through observations and interviews, while secondary data were obtained from the company in the form of production data from the Nias Tofu Product business in 2024. Data analysis was conducted using descriptive analysis techniques and the steps taken in the method analysis.MRP. According to the analysis results, the 2024 soybean raw material purchasing and demand data using the conventional method showed a shortage of raw materials of 14,200 kg with an order frequency of 14 times. Inventory management experienced inefficiencies, namely storage costs of IDR 1,600,000 and ordering costs of IDR 400,000, and raw material shortages still occurred, while the application of the MRP method resulted in order planning with an order frequency of 6 times, a fixed order quantity of 16,784 kg, and a much lower total inventory cost of IDR 335,160. The implementation of the MRP method has proven successful in eliminating raw material shortages and reducing operational costs so that the production process runs more smoothly and efficiently. This study proves that the application of MRP is effective in managing raw materials and optimizing production in the Nias Tofu business, making a significant contribution to smooth production and inventory cost efficiency.